(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study sought to explore casual workers’ posterior likelihood of being offered a permanent position at a multinational company in Zimbabwe. The study used a qualitative research approach. Data from sixteen participants who had worked for the multinational company in Zimbabwe for at least seven months were gathered using semi-structured interviews. The research found that a majority of casual work at the case multinational company in Zimbabwe see casual work as a trap than a bridge to more stable and secure positions. The three main factors identified by most of the research participants which makes casual work a trap were employer’s flexibility strategy, limited training opportunities and vertical immobility. Nonetheless, a few casual workers claimed that casual employment gives them the chance to showcase their abilities and acquire job-specific skills they need to secure full-time jobs. Hence, as it is, casual work at the case multinational company in Zimbabwe is more of a dead end than a stepping-stone to fulltime positions. The current study recommends that the case transnational firm in Zimbabwe should offer more secure contracts to some of its casual workers when there is fulltime vacancy.